Evaluation of the environmental policy and impact assessment process in Ethiopia - Ruffeis, D.; Loiskandl, W.; Awulachew, Seleshi Bekele; Boelee, Eline (Informa UK Limited, 2010)
This paper reviews the Ethiopian Environmental Policy with focus on the institutional set-up and implemented Environmental Impact Assessment (EIA) procedures. The evaluation of EIA is done against a set of evaluation criteria. Specific legal provision for EIA application is well documented and the Environmental Protection Authority exists as the legal body. A chronological evaluation of the establishment of the environmental policy reveals that this process was more a result of donor requirements than of political will. Inconsistency on institutional level, non-existence of complementarities between institutions, and of environmental and investment policy and proclamations, contradict the enforcement of the EIA law. Furthermore lack of multidisciplinary experts, missing environmental baseline data, and lack of monitoring and post-auditing adversely affect the effectiveness of the EIA law. The paper concludes that, besides other important measures, the Ethiopian EIA law needs to be adapted.